CRISPR-mediated promoter editing of a cis-regulatory element of OsNAS2 increases Zn uptake/translocation and plant yield in rice - Ludwig, Yvonne; Dueñas, Conrado; Arcillas, Erwin; Macalalad-Cabral, Reena Jesusa; Kohli, Ajay; Reinke, Russell; Slamet-Loedin, Inez H. (Frontiers in Genome Editing, 2024)
Developing nutritious rice with higher yield is one approach to alleviating the problem of micronutrient deficiency in developing countries, especially human malnutrition involving zinc (Zn) and iron (Fe) deficiency, and to achieving better adoption. Micronutrient Fe and Zn transport is mainly regulated via the nicotianamine synthase (OsNAS) gene family, whereas yield is a complex trait that involves multiple loci. Genome editing via CRISPR (clustered regularly interspaced short palindromic repeats)-Cas9 focusing on the OsNAS2 promoter, in particular the deletion of the cisregulatory element (CRE) ARR1AT at position -933, was conducted for an enhanced accumulation of Zn in the grain and per plant. The results showed that our promoter editing increased Zn per plant. The evidence also showed that improved spikelet number per main panicle led to increased grain per plant. The traits were inherited in the "transgene-free" and homozygous plant progenies. Further investigation needs to be conducted to validate trait performance under field conditions and to elucidate the cause of spikelet increase.